Soil characteristics and bare ground cover differ among jurisdictions and disturbance histories in Western US protected area-centered ecosystems - Aslan, Clare E.; Zachmann, Luke; Epanchin-Niell, Rebecca S.; Brunson, Mark W.; Veloz, Samuel; Sikes, Benjamin A. (Frontiers in Ecology and Evolution, 2022)
Ecological conditions at a given site are driven by factors including resource availability, habitat connectivity, and disturbance history. Land managers can influence disturbance history at a site by harvesting resources, creating transportation pathways, introducing new species, and altering the frequency and severity of events such as fires and floods. As a result, locations with different land management histories have also likely experienced different disturbance trajectories that, over time, are likely to result in different ecological characteristics. To understand how the presence of different management histories may shape ecological conditions across large landscapes, we examined plant and soil characteristics at matched sampling points across jurisdictional boundaries within four Protected Area-Centered Ecosystems (PACEs) in the western US. We employed Bayesian modeling to explore 1) the extent to which specific ecological variables are linked to disturbance and jurisdiction both among and within individual PACEs, and 2) whether disturbance evidence differs among jurisdictions within each PACE. Across all jurisdictions we found that disturbances were associated with ecologically meaningful shifts in percent cover of bare ground, forbs, grass, shrubs, and trees, as well as in tree species richness, soil stability, and total carbon. However, the magnitude of shifts varied by PACE. Within PACEs, there were also meaningful associations between some ecological variables and jurisdiction type; the most consistent of these were in soil stability and soil carbon:nitrogen ratios. Disturbance evidence within each PACE was relatively similar across jurisdictions, with strong differences detected between contrast jurisdictions only for the Lassen Volcanic National Park PACE (LAVO). These findings suggest an interaction between management history and geography, such that ecotones appear to manifest at jurisdictional boundaries within some, but not all, contexts of disturbance and location. Additionally, we detected numerous differences between PACEs in the size of disturbance effects on ecological variables, suggesting that while the interplay between disturbance and management explored here appears influential, there remains a large amount of unexplained variance in these landscapes. As continued global change elevates the importance of large landscape habitat connectivity, unaligned management activities among neighboring jurisdictions are likely to influence existing ecological conditions and connectivity, conservation planning, and desired outcomes.